ANALISIS FAKTOR EKONOMI DAN SOSIAL EKONOMI TERHADAP PELUANG PENYERAPAN TENAGA KERJA DI PASAR KERJA KOTA PALU - Sarmiati, Sarmiati (Katalogis, 2015)
This study aims to analyze the employment absorption which is described by economic factors, social and demographic in Palu. The analysis methods used in this research are descriptive analysis and multivariate analysis. Multivariate analysis is used with binary logistic regression model to analyze the influence factors of wages, age, gender, education level, marital status, and area of ​​residence on the opportunity of labor force absorption with applying data from Sakernas August 2011 in the city of Palu. The results show that the opportunity of labor force to fill the job vacancies in Palu in August 2011 were more higher when they are expected of high reward, aged 25-64 years, male, high school and under, married, and living in the rural areas. The most significant influence factors in this research are marital status and area of ​​residence